Desafios para a Implementação da Agenda 2030 na Amazônia - Silva, Michele Lins Aracaty e (Brasil, 2022)
The discussion about issues related to the preservation of the environment and sustainable development in the world began in the post-war period and took place through the Stockholm Conference, Sweden, in 1972, known as the United Nations Conference on the Environment. Subsequently, numerous other world meetings took place in order to implement environmental management policies involving the main world powers in an attempt to reduce negative environmental impacts. The most recent collective construction, signed in 2015, is the 2030 Agenda (composed of 17 global goals), which constitutes a commitment by member countries to be implemented in the form of actions over the next 15 years (until 2030), having as a pillar the collaborative effort (governments, companies, academia and civil society). Following the example of other countries, in Brazil and in the Amazon, working groups were formed to implement actions with the communities, based on the global objectives. Thus, we aim to analyze the implementation of Agenda 2030 actions in the Amazon context; carry out a history of conferences on climate and sustainable development over the years; raise the main objectives that make up the 2030 Agenda as well as raise the main actions regarding the implementation of the objectives in the Amazonian context. Therefore, this research is bibliographic and documentary, using material already published to build the theoretical basis and UNDP and UN documents to present the advances of the 2030 Agenda in the Amazon context.